Semimetallic Bismuthene with Edge-Rich Dangling Bonds Broad-Spectrum-Driven and Edge-Confined Electron Enhancement Boosting CO2 Hydrogenation Reduction - Wang, Bin (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 The Authors. Advanced Materials published by Wiley‐VCH GmbH.